Remarks on the Parameters of Argument Ellipsis: A New Perspective from Colloquial Singapore English. (27th September 2016) - Sato, Yosuke
Abstract: In this paper, I investigate the nature of parameters responsible for the distribution of argument ellipsis (AE) from the perspective of Colloquial Singapore English (CSE). One recent theory by Saito (2007) suggests that this process, technically analyzed through LF‐Copy, is blocked by ϕ‐feature agreements of T with subject DPs and v with object DPs, respectively. I provide evidence from Case marking, VP‐ and CP‐ellipsis, and Exceptional Case‐Marking constructions that in CSE both functional heads possess abstract ϕ‐feature agreement, as in Standard English. The agreement theory predicts that neither the null subject nor null object position should permit AE in CSE. The fact, however, is that AE is blocked in subject positions but permitted in object positions. I propose that AE in CSE is controlled, instead, by the presence of an operator–variable topic chain, formed to reflect the language's topic‐prominent profile, as manifested in its definite subject preference. This analysis is supported by the observation that the null subject position allows AE in CSE as long as it is not linked to the topic position, as in the case of the hanging topic construction. The alternative analysis suggests that the cross‐linguistic distribution of AE is conditioned by (at least) two parameters: agreement and topichood.